1986
DOI: 10.1111/j.1365-3040.1986.tb01572.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental tests of the Münch–Horwitz theory of phloem transport: effects of loading rates*

Abstract: Extended square-wave traeer kinetics using "CO2 were used to measure the speed of transport and activity level (proportional to concentration) in the phloem at high and low loading rates in six species of plants. In all cases, increased loading rates resulted in inereased concentration. In most cases speed also increased, however, in two cases speed was lower and tracer activity was much higher at the higher loading rate. All the responses are consistent with the Milnch-Horwitz theory of phloem transport, depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Second, changes in the rate of phloem loading resulting from changes in photosynthetic production may have significant effects on phloem sucrose concentrations independent of sink demand. Magnuson, Goeschl & Fares (1986), working with 11 C tracers, obtained results that suggest that phloem sugar concentrations change in response to diurnal changes in phloem loading and changes in CO 2 concentration. Third, changes in water potential gradients between sinks and sources may require large changes in phloem osmotic concentration gradients to maintain flux even when there is no change in sink demand (Boersma, Lindstrom & Childs 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Second, changes in the rate of phloem loading resulting from changes in photosynthetic production may have significant effects on phloem sucrose concentrations independent of sink demand. Magnuson, Goeschl & Fares (1986), working with 11 C tracers, obtained results that suggest that phloem sugar concentrations change in response to diurnal changes in phloem loading and changes in CO 2 concentration. Third, changes in water potential gradients between sinks and sources may require large changes in phloem osmotic concentration gradients to maintain flux even when there is no change in sink demand (Boersma, Lindstrom & Childs 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, modeling (Tyree et al, 1974; and empirical studies (Passioura & Ashford, 1974;Magnuson et al, 1986) have shown the OGPF hypothesisFin its simplest formFto be a virtual certainty for small plants. Additionally, the relatively recent recognition that sieve plates are nominally clear of P-proteins further justifies this certainty (Knoblauch & van Bel, 1998;Eckardt, 2001;Knoblauch et al, 2001), and has only bolstered the study of assimilate loading in source tissues (van Bel & Gamalei, 1992;van Bel, 1993;Komor et al, 1996;Turgeon & Medville, 1998;Patrick et al, 2001) and unloading in sink tissues (Oparka, 1990;Farrar, 1993;Minchin & Thorpe, 1996;Patrick, 1997;Oparka & Turgeon, 1999;Oparka & Cruz, 2000), as well as the molecular biology of the transfer of water, sucrose, and aminenitrogen between the phloem and xylem (Patrick et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The studies on phloem loading rate at the whole plant level were very few. They were based mostly on 11C experiments (Magnuson et al 1986, Thorpe and Minchin 1987, Farrar et al 1994, the carbon isotope with half live of several minutes, which allow the repetition of a few experiments on the same plant and to study the effect of che~rfical and physical stimuli. However, studies with lie cause many logistical problems and are possible only in laboratories located near the nuclear reactor where the I1C is synthesised (Magnuson et al 1982).…”
Section: Introductionmentioning
confidence: 99%